Are the causes of obesity primarily environmental? No. (11th September 2012) - Frayling, Timothy M
Abstract : John Wilding (doi:10.1136/bmj.e5843 ) believes that changes in our environment are responsible for increasing obesity but Timothy Frayling thinks that it is genetic factors that determine who gets fat